The benefits of mobile health APP in improving the rate of standardized treatment of gonorrhea - Boling LU; Wei ZHOU; Lifang WEN; Fang LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To evaluate the benefits of mobile health APP in improving the rate of standardized treatment of gonorrhea. Methods This study included 80 doctors from People's Hospital of Shenzhen Luohu district. These doctors were randomly divided into two groups, 40 doctors in the intervention and 40 doctors in the control group. In the intervention group, online video training on the latest treatment guidelines of gonorrhea was given to the doctors, using mobile health app, for the total of 18 months, while the control group was trained using traditional offline courses. The rates of standardized treatment of gonorrhea were compared before and after the training in both groups. Results Prior to the training, the rates of standardized treatment of gonorrhea did not differ significantly between the two groups (χ2=0.06, P=0.801). After the training, the rate of standardized treatment of gonorrhea was significantly higher in the intervention group than in the controls (χ2=8.71, P=0.003), although both training approaches improved the rates of standardized treatment (both P<0.05). Conclusion The mobile health APP can improve the rate of standardized treatment of gonorrhea.